(untitled) (Revista Iberoamericana de Bioética, 2024)
Inequity in health and medical care increase constantly; neither human rights, including the right to healthcare, nor global bioethics manage to mitigate or raise awareness of their damaging consequences. This text proposes medicine as a common good, thus requiring a common anthropology, expressed as three transcendental anthropological conditions to ensure survival and social integration: relationality, mundane transcendence, and transcendence of self. These conditions pertain to the lived body, which perceives the environment and the living body that acts in and on the world. Perception and action are susceptible to dysfunctional damage. It falls to medicine to care for, cure and rehabilitate the damaged body. Medicine ought therefore to be a common good, indiscriminately accessible and available to every human being.